The human animal a personal view of the human species - Booth, Graham ([S.l.] : BBC Productions, 1994)
Desmond Morris, one of the most original, accessible and popular scientists of modern times, peels away the layers of cultural, religious and social conditioning to reveal Homo sapiens in his true colours.
Editor, Stuart Napier ; series producer, Mike Beynon
Narrator: Desmond Morris
Keywords: Human beings -- Animal nature; Men